THE CONTRIBUTION OF BUMI MANUSIA NOVEL BY PRAMOEDYA ANANTA TOER TOWARDS INDONESIAN HISTORY UNDERSTANDING - Jurahman, Yohanes B. (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2016)
literature work in from of a novel was always related to creator ability in fictioning and its imaginative work. While the history could not be separated from facts and events occured in the past. When literature and history were discussed jointly, it would emerge a question whether there was a fact in novel? Novel and history would be debated when entering world of construction, reconstruction and deconstruction. A storying construction of an event in novel and history was basically different. The novel entlited Bumi Manusia (Human Earth) written by Pramoedya Ananta Toer was a native young struggle named Minke who had a nationalism spirit and high patriotism. Pramoedya Ananta Toer had a skill in building a story in his work.as a literature work (history novel) based on Indonesian history in the end of XIX century, had an excellence in a narrative subject that was able to bring readers as if exploring the real story. Based on findings from the reader reception result, it obtained a historical data such as story figure names, place names and storying period selection. For the histories, this novel provided a richness especially related to the understanding towards situation, condition, and enthusiasm and era spirit. The Bumi Manusia novel provided an inspiration and illustration on Indonesian situation and condition in the end of XIX century era. Therefore from historical point of view, it could be utilized in improving a historical science. This work was a letter literature treasure that had literature values and also a high history. Its existence as a literature document that had an important position in Indonesian literature history. By utilizing setting of figure, place, event that was performed seriously was able to yield big works in Indonesian literature world so that could provide a valuable contribution for Indonesian history understanding in the related periods